1983
DOI: 10.2337/diab.32.10.894
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus in Hopi and Navajo Indians: Prevalence of Microvascular Complications

Abstract: In a cross-sectional study of Hopi and Navajo Indians with non-insulin-dependent diabetes mellitus, we found vascular complications to be strongly related to the duration of diabetes. In patients with diabetes of at least 10 yr duration, retinopathy was found in 57%, nephropathy in 40%, peripheral neuropathy in 21%, and peripheral vascular disease in 28%. For the Hopi and Navajo, the duration-specific prevalence rates of microvascular disease were very similar to prevalence rates found in many other population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

1984
1984
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(4 citation statements)
references
References 5 publications
(7 reference statements)
1
1
2
Order By: Relevance
“…The prevalence of DR in these earlier studies was higher than that reported here, i.e., in Pima Indians with type 2 diabetes [ 3 ], Navajo and Hopi Indians [ 4 ], and Sioux Indian tribes [ 5 ], the prevalence of NPDR was 37.8%, 40%, and 45.3% respectively. The prevalence of PDR was 2.7% (Pima), and prevalence of vision-threatening retinopathy was 8.2% (Navajo and Hopi).…”
Section: Discussioncontrasting
confidence: 59%
“…The prevalence of DR in these earlier studies was higher than that reported here, i.e., in Pima Indians with type 2 diabetes [ 3 ], Navajo and Hopi Indians [ 4 ], and Sioux Indian tribes [ 5 ], the prevalence of NPDR was 37.8%, 40%, and 45.3% respectively. The prevalence of PDR was 2.7% (Pima), and prevalence of vision-threatening retinopathy was 8.2% (Navajo and Hopi).…”
Section: Discussioncontrasting
confidence: 59%
“…Prevalence rates in various studies from around the world show considerable variation as a result of variations in study design, detection methods, the examination of patients at different stages in the natural history of diabetes, or in the definition of PN, and the study of selected populations, from as low as 1.5% to as high as 100% (7,(11)(12)(13)(14)(15)(16) making comparisons between studies of limited value. Our clinic-based prevalence is higher than the values reported in studies undertaken in developed nations (4,8,12,15,17,(23)(24)(25)(26)(27). In a Turkish study the overall prevalence of neuropathy in patients with type 2 diabetes was 60% (25).…”
Section: Discussioncontrasting
confidence: 53%
“…Mean duration of diabetes in our population was 11.2 years. One study of north-eastern Arizona found neuropathy in 21% of people with diabetes with more than 10-year duration of disease [30]. Consistent with the other studies our study confirms the association between the incidence rate of neuropathy, age and duration of diabetes [31].…”
Section: Discussionsupporting
confidence: 91%